Employer Offered Family Support Programs, Gender and Voluntary and Involuntary Part-Time Work - U. Zeytinoglu, Isik; B. Cooke, Gordon; L. Mann, Sara (Relations industrielles / Industrial Relations, 2010)
This paper examines the availability of employer offered childcare and eldercare support in Canada. In addition, the associations between these support programs, gender and voluntary and involuntary part-time work are also examined. Using Statistics Canada’s 2003 Workplace and Employee Survey, results show that employer offered childcare programs exist in a very small number of workplaces, and eldercare support programs are almost nonexistent. Moreover, women are less likely than men to be offered family support programs. Voluntary and involuntary part-time workers are less likely to be offered family support programs than full-time workers. We argue that if individuals are going to receive assistance for childcare and eldercare, that assistance is more likely going to come from the government as opposed to employers. We suggest publicly funded universal family support programs to assist workers.